PENGARUH RASIO KEUANGAN DAN NON KEUANGAN PADA KINERJA KEUANGAN PERBANKAN - Victoria, Ni Putu Lia; Erawati, Ni Made Adi (E-Jurnal Akuntansi; Vol 13 No 2 (2015), 2015)
National growth of a country, where economic development including, requiring the participation of financial institutions to finance the construction. Financial institutions have an important role in the development of the country, where financial institutions are needed as a financial institution or lending. Viewing of its important role, financial institutions are required to improve the ability to compete and watch the bank's financial performance. This study aims to determine the level of cash flows, debt management effectiveness, ROA, the level of outstanding loans, and the cost of corporate social responsibility on the financial performance of banks in IDX. Data collection methods used in this research is based on books and financial reports. The result of this study showed that the level of cash flows, the effectiveness of debt management, the level of outstanding loans, and the positive impact of CSR costs, while BOPO negative effect on the financial performance of banking companies listed on the Stock Exchange in 2009 -2013.
Keywords: cash flow, CAR, BOPO, LDR, CSR costs, ROA